Immunolocalization of Phospholipase C Zeta 1 in Water Buffalo Sperm and Its Role in Oocyte Activation - Tadeo, Roseline D.; Atabay, Edwin C.; Atabay, Eufrocina P. (Journal of Buffalo Science, 2025)
The present study aimed to investigate the expression and localization of Phospholipase C zeta 1 (PLCZ1) in water buffalo sperm and determine its localization pattern following the induction of early fertilization events. Initially, water buffalo semen under uncapacitated conditions underwent western blot analysis to detect and localize the PLCZ1 protein via immunofluorescence, utilizing antibodies specific to buffalo PLCZ1. In a parallel experiment, a subset of sperm underwent in-vitro capacitation in a medium containing bicarbonate, followed by treatment with a calcium ionophore to induce the acrosome reaction, providing evidence of capacitation. The findings revealed the detection of PLCZ1 as an immunoreactive band at approximately 77 kDa in buffalo sperm. Furthermore, immunolocalization of PLCZ1 in uncapacitated buffalo sperm showed predominant expression in the acrosome and post-acrosomal regions, with minimal reactivity in the tail region. Conversely, capacitated buffalo sperm exhibited a shift in PLCZ1 localization, with a prominent presence at the acrosomal cap region of the sperm head and reduced reactivity in the tail region. This translocation of PLCZ1 in capacitated sperm suggests early physiological activities, particularly in inducing calcium oscillation to initiate oocyte activation during fertilization. Moreover, the successful detection of PLCZ1 in buffalo sperm in the present study highlights its potential as a biological marker for screening bull fertility and genetic improvement in water buffaloes.